Financial Crises, Macroeconomic Shocks, and the Government Balance Sheet : A Panel Analysis - Ruzzante, Matteo (IMF Working Papers; Working Paper ;, 2018)
Government financial assets are increasingly recognized as playing an important role in assessing fiscal sustainability. However, very little research has been done on the dynamics of government financial assets compared to liabilities. In this paper, we investigate the impact of recent financial crises and macroeconomic shocks on government balance sheets, decomposing the separate effects on financial assets and liabilities. Using quarterly Government Finance Statistics (GFS) data, we analyze a panel of 27 countries over the period 1999Q1-2017Q1 through fixed effects and panel VAR techniques. Financial crises are shown to deteriorate the net financial worth of governments, but no significant impact is found on assets suggesting that they are not being used as fiscal buffers in bad times. On the contrary, countries that suffered both financial and banking crises experienced an 'artificial' increase of their asset position through bank bailouts. Macroeconomic shock analyses reveal that government balance sheet items are countercyclical, but important asymmetries are found in their dynamics.